CLONING AND SEQUENCE ANALYSIS OF A PUTATIVE CCT-MOTIF GENE IN TEN FOXTAIL MILLET CULTIVARS - X.P. Jia; J.Y. Bai; B.Y. Fan; G.N. Zhang; G.A. Shi; D.Y. Hou J.Z. Quan; Z.P. Dong (Journal of Animal and Plant Sciences, 2016)
CCT-motif genes are key genes participating in photoperiod-control plant flowering, and proved to be closely related to crop production. In this study, a putative foxtail millet CCT-motif gene was cloned in ten cultivars, and seven agronomic traits of these cultivars were investigated. The results showed that totally 34 mutation sites including 33 SNPs and 1 InDel (insertion-deletion) were detected in coding region of CCT-motif gene among the ten cultivars, which led to sixteen aa substitution and one aa insertion/deletion among CCT-motif gene protein sequences of 10 foxtail millet cultivars. According to the mutation types of CCT-motif gene protein sequences, ten foxtail millet cultivars could be divided into seven genotypes. The nucleotide polymorphism value (θ) of CCT-motif gene coding sequence was 0.017, indicating the low diversity level of this gene in selected ten foxtail millet cultivars. The Tajima’D value was 0.998, greater than zero, indicating the CCT-motif gene subject to natural selection during evolutionary process. LD analysis showed that a large LD structure including twenty mutation sites was existed in coding region. All of the results above gave valuable information for launching association analysis study between the CCT-motif gene and main agronomic traits in foxtail millet. The mutation information in coding region of CCT-motif gene provided valuable clue for further discovering function altering mechanism of this gene. Seven agronomic traits, days to heading (DH), plant height (PH), panicle length (PL), ear diameter (ED), branch number per panicle (BNP), grain number per branch (GNB) and 1000-grain weight (1000-GW), ranged from 38 to 74, from 56.8 to 128.7, from 6.8 to 21.6, from 3.0 to 7.6, from 58 to 113, from 7 to 72, from 0.7 to 2.8 respectively, indicating abundant genetic variation existed among the ten selected cultivars. Association analysis showed that three mutation sites, locus 109, locus 161, locus 424 were associated with 1000-grain weight (1000-GW), one mutation site, locus 588, was associated with panicle length (PL). Conclusion: cloned a putative CCT-motif gene in foxtail millet, this gene showed low diversity level and subject to natural selection during evolutionary process. Four mutation sites in CCT-motif gene coding region associated with1000-GW and PL.
Keywords: Foxtail millet; CCT-motif gene; SNPs; LD analysis; Association analysis